Effects of Difference Age and Information Searching Level on Attitudes toward Innovative Product - Lee, Sinae; Min, Dongwon (Asia Marketing Journal (Online), 2023)
Innovation is no longer the purview of high-tech industries; it is blossoming in the home appliances and cosmetics sectors. However, consumers’ anxiety about the risk of new products prevents them from reaping the benefits of innovation. This anxiety is driven by customer’s lack of prior information on new products. This study examines how difference age between the chronological age of consumers and their cognitive age affects consumers’ willingness to search for information on innovative products, leading to reduced new-product anxiety. According to a survey of participants who actually bought an innovative product, we found that participants searched for more information when they perceived themselves to be younger than their chronological age (a high difference age). Where participants did not proactively search for information (due to a low difference age), they could be encouraged to do this through marketing campaigns. Together, these findings expand our understanding of how consumers’ difference age can be leveraged in digital marketing to enable companies to more strategically reach consumers when planning or launching innovative products.